HISTOPATHOLOGY OF WATERMELON ROOT INFECTED WITH ROOT-KNOT NEMATODE (Meloidogyne spp.) IN KWARA STATE, NIGERIA - Apalowo, Oluropo Ayotunde; Izuogu, Nkechi Betsy; Baba, Halimat Shola; Olajide, Comfort Motunrayo; Balogun, Olusegun Samuel; Nnabuihe, Emmanuel Chinweike; Okafor, Maduabuchi Johnbosco (FUDMA JOURNAL OF SCIENCES, 2025)
This study was carried out to determine the feeding pattern of root-knot nematode (RKN) infecting the root of watermelon in Ilorin, Nigeria. A commonly cultivated variety, kaolak was obtained and planted in a screen house. The screenhouse experiment was set out in a Completely Randomized Design (CRD). Two treatments were used; inoculated and uninoculated seedlings. Each treatment was replicated thirty times, making a total of sixty treatment combinations. Roots from each treatment were removed and cut into 4 to 5 cm pieces. The root materials were immediately fixed in formalin-aceto-alcohol (FAA). Results of this experiment showed the disorganization of the vascular tissue in the infected root. Visible galls were observed in the roots after 29 days which revealed similarity in feeding and reproduction of root-knot nematode in parasitized plant. The study advanced our knowledge on RKN feeding pattern in watermelon and the cosmopolitan nature of the pathogen.